2019
DOI: 10.1021/acs.jmedchem.9b00969
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 4-Methylquinazoline Based PI3K Inhibitors for the Potential Treatment of Idiopathic Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive and fatal lung disease, and its molecular pathogenesis remains poorly understood. Recently, emerging evidence demonstrates that the PI3K signaling transduction pathway is linked to the pathology of IPF. In this work, we rationally designed a new series of 4-methylquinazoline derivatives as highly potent PI3K inhibitors that significantly suppress the phosphorylation of the main PI3K downstream effectors and displays marked antiproliferative activity in mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Three drugs target the PI3K signaling pathway, and many other experimental trials have also achieved promising results. A summary of these drugs is shown in Table 1 49 , 62 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 .…”
Section: Potential Drugs Targeting Pi3k/akt For Ipf Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Three drugs target the PI3K signaling pathway, and many other experimental trials have also achieved promising results. A summary of these drugs is shown in Table 1 49 , 62 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 .…”
Section: Potential Drugs Targeting Pi3k/akt For Ipf Treatmentmentioning
confidence: 99%
“… Agent Mechanism/target Function description Phase of development and status Common adverse event Ref. GSK2126458 PI3K/mTOR inhibitor Reduce TGF- β -induced fibroblast proliferation and collagen I synthesis Phase I completed (NCT01725139) Diarrhoea, hyperglycaemia, nausea 166 HEC68498 PI3K inhibitor Anti-fibrosis and anti-inflammation Phase I Active, not recruiting (NCT03502902) Not described / Rapamycin mTOR inhibitor Inhibit TGF- α and EGFR signaling NA, completed (NCT01462006) Hyperglycemia, hypophosphatemia, anemia 167 PX-866 pan-PI3K inhibitor Inhibit TGF- α Pre-clinical Rash, hyperglycemia, trans-aminase elevations 168 Derivatives of 4-methylquinaz-oline PI3K inhibitor Anti-fibrosis and anti-inflammation Pre-clinical Not described 169 LY294002 AKT inhibitor Inhibit fibroblasts expansion and fibronectin matrix formation Pre-clinical Not described 49 ASV TGF β 1/PI3K/AKT pathway inhibition Inhibit EMT Pre-clinical Raised total bilirubin and rash 170 , 171 Hyp AKT/GSK3 β pathway inhibition Inhibit inflammation, oxidative stress and EMT Pre-clinical Not described 172 Ligustrazine PI3K/AKT/mTOR pathway inhibition Reduce ROS Pre-clinical Edema, hypertension, gastrointestinal bleeding 62 , 173 Quercetin PI3K/AKT pathway inhibition …”
Section: Potential Drugs Targeting Pi3k/akt For Ipf Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of PF by blocking the Pi3k/Akt signaling pathway could potentially be a new direction for the treatment of PF. It was found that Pi3k inhibitors exhibited superior proliferation inhibitory activity against mouse MLG2908 lung fibroblasts and were able to improve lung function and pathological damage in mice with PF, and reduce hydroxyproline content and α-SMA levels in lung tissue [29,30]. Our results have demonstrated that Danhong injection can attenuate the protein expression of phosphorylated Pi3k and Akt in the lung tissue of PF mice.…”
Section: Discussionmentioning
confidence: 51%
“…The synthesis of compound 1 was performed as follows. Compound 2 (54 mg, 0.1 mmol, 1.0 equiv), which was prepared as we previously reported, 33 was dissolved in DMF (2 mL) along with K 2 CO 3 (28 mg, 0.2 mmol, 2.0 equiv). 1-(Bromomethyl)-4,5-dimethoxy-2-nitrobenzene (41 mg, 0.15 mmol, 1.5 equiv) was then added into the reaction mixture, which was stirred at room temperature for 2 h. When compound 2 was completely consumed, the reaction mixture was filtered and concentrated under a vacuum.…”
Section: ■ Conclusionmentioning
confidence: 99%